2007
DOI: 10.1002/path.2097
|View full text |Cite
|
Sign up to set email alerts
|

Morphology, mechanisms and pathology of musculoskeletal ageing

Abstract: In general terms, the recognized alterations in circulating humoral factors (hormones, cytokines, growth factors) that occur in ageing, coupled with innate cellular senescence exaggerated by the slow turnover of many connective tissue cell populations and the ageassociated alterations in matrix molecule cross-linking, predispose the elderly to altered connective tissue biology. These changes can be profound, leading to poor mobility, altered ability to withstand cold, weakness and an increased risk of falls, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
66
0
9

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(79 citation statements)
references
References 88 publications
4
66
0
9
Order By: Relevance
“…The SST consists of dichotomous (yes [1] or no [0]) response options. For each question, the patients indicate that they are able or are not able to do the activity.…”
Section: Outcome Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…The SST consists of dichotomous (yes [1] or no [0]) response options. For each question, the patients indicate that they are able or are not able to do the activity.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…Bony changes have a direct effect on joint mobility, influencing the joint surfaces to alter joint mechanics [1]. Subchondral bone (the layer directly below No matter how healthy an individual is, as they age their joints will show some changes in mobility, due to changes in the connective tissues.…”
mentioning
confidence: 99%
“…A higher stiffness limits the movements of flexion and extension and consequently, reduces the range of motion. Freemont and Hoyland (2007) listed the main age-dependent factors affecting musculoskeletal tissues: bones become more fragile, cartilage loses resilience, skeletal muscles become weaker, ligaments lose elasticity, and fat is redistributed. Lacraz et al (2015) reported that, in mice, muscle stiffness increases with age due to the deposition of extracellular matrix, which influences the microenvironment of myogenic precursor cells (stem cells that act in cell turnover).…”
Section: A B Discussionmentioning
confidence: 99%
“…However, sarcopenia occurs in senescence, which leads to muscle wasting and loss of strength. Loss of motor end plates results in a decrease of innervation which, together with reduced anabolic hormones and increased catabolic agents, increases the muscle loss rate (FREEMONT;HOYLAND, 2007). Therefore, Sabanci and Ocal (2016) in a study of the stifle joint in seven dog breeds, reported that breed differences, body weights, and muscle mass should be taken into consideration during goniometric assessment of stifle function.…”
Section: A B Discussionmentioning
confidence: 99%
See 1 more Smart Citation